How Does Coastal Gravel Get Sorted Under Stormy Longshore Transport?. Issue 21 (8th November 2021) - Eyal, H.; Enzel, Y.; Meiburg, E.; Vowinckel, B.; Lensky, N. G.
Abstract: Storm waves transport and sort coarse gravel along coasts. This fundamental process is important under changing sea‐levels and increased storm frequency and intensity. However, limited information on intra‐storm clast motion restricts theory development for coastal gravel sorting and coastal management of longshore transport. Here, we use smart boulders equipped with loggers recording underwater, real‐time, intra‐storm clast motion, and measured longshore displacement of varied‐mass marked boulders during storms. We utilize the unique setting of the Dead Sea shores where rapidly falling water levels allow isolating boulder transport during individual storms. Guided by these observations, we develop a new model quantifying the critical wave height for a certain clast mass mobilization. Then, we obtain an expression for the longshore clast displacement under the fluid‐induced pressure impulse of a given wave. Finally, we formulate the sorting enforced by wave‐height distributions during a storm, demonstrating how sorting is a direct manifestation of regional hydroclimatology. Plain Language Summary: Beaches connect terrestrial and marine environments, frequently near large population centers. Sea‐level rise and increased storm intensities threaten this environment, causing enhanced coastal erosion and damage to cities and infrastructure, along with loss of coastal tourism. We combine real‐time measurements of clast movement during a storm with a newly‐developed theoretical model. This allows predicting longshore sediment transport and determine critical wave heights for mobilization and alongshore movement of various clast sizes under a distribution of wave heights. The outcome is a quantitative, process‐based tool for coarse‐gravel motion and beach evolution, a key for coastal management. We show how the wave‐induced pressure force and impulse exerted on clasts dictates the longshore clast motion and sorting, and how sorting is a direct manifestation of regional hydroclimatology. Key Points: Storm waves sort clasts according to mass along the shores of the Dead Sea; clast motion is traced by marked and smart boulders A newly developed model predicts the critical wave height for motion initiation and the total longshore transport of cobbles‐boulders Coastal sorting is a direct manifestation of regional hydroclimatology, derived by hydrodynamic pressure‐induced impulse exerted on clasts